Improved Physical Health of Children During The Covid-19 Pandemic in Banjarmasin - Suci Fitri Rahayu (Borneo Community Development, 2021)
Malnutrition or severe wasting is the most dangerous malnutrition problem, because it increases the risk of child mortality up to 12 times. Children who suffer from malnutrition also experience a higher risk of becoming stunted and also in the long term will affect growth, brain development and also the ability to earn a living as an adult. The COVID-19 pandemic is expected to significantly increase the risk of children experiencing malnutrition and potentially worsen the existing conditions given that various access to health services, access to food and interventions that can be done to improve the nutritional health of children in Indonesia are hampered. Child development services are very important because developmental disorders detected early will receive appropriate interventions. The main activities to monitor children's growth and development have stopped being implemented in health services or schools. From the results of observations in the Banjarmasin City Region, it was found that activities in monitoring children's growth and development were less than optimal during the COVID-19 pandemic. The purpose of this community service activity is to improve physical health during the COVID-19 pandemic by physical examination of children and providing additional nutrition at school. The method starts from a physical examination and providing additional nutrition at school. The activity was carried out in August 2021. The activity was carried out at the Banjarmasin City Regional Elementary School. This activity was attended by 32 children. The implementation of the activities went well and smoothly. This activity raised a theme "Improving Physical Health in Children during the COVID-19 Pandemic in the Banjarmasin City Area". This activity is carried out to improve physical health in children during the COVID-19 pandemic. This activity is carried out openly in the school yard to prevent crowds and in accordance with health protocols. In this activity, physical examination and distribution of additional nutrients for children such as milk and other complementary foods were carried out. The results of this community service activity obtained that the physical health of the child was in good and normal condition and the distribution of additional food was distributed individually to the child. The follow-up plan for this activity is Mental Health Improvement in Children during the COVID-19 Pandemic. The recommendation for the school is to always monitor the development and growth of children at school once a month to find out early if there are disturbances in growth and development.